2009
DOI: 10.1186/1741-7015-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and copper supplementation in acute diarrhea in children: a double-blind randomized controlled trial

Abstract: Background: Diarrhea causes an estimated 2.5 million child deaths in developing countries each year, 35% of which are due to acute diarrhea. Zinc and copper stores in the body are known to be depleted during acute diarrhea. Our objectives were to evaluate the efficacy of zinc and copper supplementation when given with standard treatment to children with acute watery or bloody diarrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 38 publications
3
72
1
4
Order By: Relevance
“…Study characteristics are shown in Table 1 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Only three studies had a population of fewer than 100 patients, and all studies were conducted in countries considered to be "emerging and developing economies" (48).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are shown in Table 1 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Only three studies had a population of fewer than 100 patients, and all studies were conducted in countries considered to be "emerging and developing economies" (48).…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity analysis also showed that one study (43) contributed considerably toward the heterogeneity detected in the outcomes of diarrhea on days 3, 5, and 7. This outcome might be due to low adherence to the treatment in the study, which may have contributed to a smaller effect of the use of zinc in the population assessed.…”
Section: Heterogeneitymentioning
confidence: 92%
“…Some authors showed distinct interrelation between frequency of diarrheal disease episodes and low plasmatic level of coper and zinc. Besides, there are data proving the fact that copper deficiency is more widespread than zinc deficiency [19]. Zinc tends to be involved into competitive relations with some other metals.…”
Section: (86)2016 інфекційні хворобиmentioning
confidence: 99%
“…[8][9][10] Also the expected beneficial effects of Zinc supplementation for acute diarrhea were not observed in a study on Zinc and Copper supplementation in acute diarrhea in children [11]. Also a therapeutic study from Bangladesh on infants Showed that age can modify the beneficial effect of Zinc supplementation.…”
Section: Introductionmentioning
confidence: 99%